Responsible innovation across borders: tensions, paradoxes and possibilities - Macnaghten, P.; Owen, R.; Stilgoe, J.; Wynne, B.; Azevedo, A.; de Campos, A.; Chilvers, J.; Dagnino, R.; di Giulio, G.; Frow, E.; Garvey, B.; Groves, C.; et al. (Taylor & Francis, 2014)
In March 2014 a group of early career researchers and academics from São Paulo state and from the UK met at the University of Campinas to participate in a workshop on ‘Responsible Innovation and the Governance of Socially Controversial Technologies’. In this Perspective we describe key reflections and observations from the workshop discussions, paying particular attention to the discourse of responsible innovation from a cross-cultural perspective. We describe a number of important tensions, paradoxes and opportunities that emerged over the three days of the workshop.